Spirulina maxima Derived Pectin Nanoparticles Enhance the Immunomodulation, Stress Tolerance, and Wound Healing in Zebrafish - Dinusha C. Rajapaksha; Shan L. Edirisinghe; Chamilani Nikapitiya; SHS Dananjaya; Hyo-Jung Kwun; Cheol-Hee Kim; Chulhong Oh; Do-Hyung Kang; Mahanama De Zoysa (Marine Drugs, 2020)
In this study, Spirulina maxima derived pectin nanoparticles (SmPNPs) were synthesized and multiple biological effects were investigated using in vitro and in vivo models. SmPNPs were not toxic to Raw 264.7 cells and zebrafish embryos up to 1 mg/mL and 200 µg/mL, respectively. SmPNPs upregulated Il 10, Cat, Sod 2, Def 1, Def 2, and Muc 1 in Raw 264.7 cells and tlr2, tlr4b, tlr5b, il1β, tnfα, cxcl8a, cxcl18b, ccl34a.4, ccl34b.4, muc5.1, muc5.2, muc5.3, hamp, cstd, hsp70, cat, and sod1 in the larvae and adult zebrafish, suggesting immunomodulatory activity. Exposure of larvae to SmPNPs followed by challenge with pathogenic bacterium Aeromonas hydrophila resulted a two-fold reduction of reactive oxygen species, indicating reduced oxidative stress compared to that in the control group. The cumulative percent survival of larvae exposed to SmPNPs (50 µg/mL) and adults fed diet supplemented with SmPNPs (4%) was 53.3% and 76.7%, respectively. Topical application of SmPNPs on adult zebrafish showed a higher wound healing percentage (48.9%) compared to that in the vehicle treated group (38.8%). Upregulated wound healing markers (tgfβ1, timp2b, mmp9, tnfα, il1β,ccl34a.4, and ccl34b.4), enhanced wound closure, and restored pigmentation indicated wound healing properties of SmPNPs. Overall, results uncover the multiple bioactivities of SmPNPs, which could be a promising biocompatible candidate for broad range of aquatic and human therapies.